Collins common errors in English : your essential guide to accurate English - Walter, Elizabeth, 1961; Woodford, Kate (Glasgow, Scotland: Collins, 2015)
Focussing on the most common errors in English, this book is the easiest way to improve your everyday language skills. Using simple explanations and corpus examples, it uses a thematic approach to steer learners away from the most common pitfalls in English. This invaluable guide is suitable for learners of English wishing to improve their accuracy and avoid the most basic mistakes. The book offers help with Spelling and Punctuation, and covers the major parts of speech in depth. It offers clear guidance on word choice and confusable words. A comprehensive exercise section also reinforces the key points for each thematic section. What's more, its clear, thematic layout makes information easy to find and understand. Suitable for learners of English with a pre-intermediate to intermediate level of English (A2-B2), but who want to improve their accuracy by overcoming the most common mistakes made by non-native speakers of English
Keywords: English language -- Grammar; English language -- study and teaching; English language -- Errors of usage